Subsidise the test, the treatment or both? Results of an individually randomised controlled trial of the management of suspected malaria fevers in the retail sector in western Kenya. Issue 11 (3rd November 2020) - Laktabai, Jeremiah; Saran, Indrani; Zhou, Yunji; Simmons, Ryan A; Turner, Elizabeth L; Visser, Theodoor; O'Meara, Wendy
Abstract : Introduction: In many malaria-endemic countries, the private retail sector is a major source of antimalarial drugs. However, the rarity of malaria diagnostic testing in the retail sector leads to overuse of the first-line class of antimalarial drugs known as artemisinin-combination therapies (ACTs). The goal of this study was to identify the combination of malaria rapid diagnostic test (RDT) and ACT subsidies that maximises the proportion of clients seeking care in a retail outlet that choose to purchase an RDT (RDT uptake) and use ACTs appropriately. Methods: 842 clients seeking care in 12 select retail outlets in western Kenya were recruited and randomised into 4 arms of different combinations of ACT and RDT subsidies, with ACT subsidies conditional on a positive RDT. The outcomes were RDT uptake (primary) and appropriate and targeted ACT use (secondary). Participants' familiarity with RDTs and their confidence in test results were also evaluated. Results: RDT uptake was high (over 96%) across the study arms. Testing uptake was 1.025 times higher (98% CI 1.002 to 1.049) in the RDT subsidised arms than in the unsubsidised groups. Over 98% of clients were aware of malaria testing, but only 35% had a previous experience with RDTs. Nonetheless, confidence in the accuracy of RDTs was high. We found high levels of appropriate use and targeting of ACTs, with 86% of RDT positives taking an ACT, and 93.4% of RDT negatives not taking an ACT. The conditional ACT subsidy did not affect the RDT test purchasing behaviour (risk ratio: 0.994; 98% CI 0.979 to 1.009). Conclusion: Test dependent ACT subsidies may contribute to ACT targeting. However, in this context, high confidence in the accuracy of RDTs and reliable supplies of RDTs and ACTs likely played a greater role in testing uptake and adherence to test results.